Visualizing value for money in public health interventions. (23rd January 2018) - Leigh-Hunt, Nicholas; Cooper, Duncan; Furber, Andrew; Bevan, Gwyn; Gray, Muir
Abstract: Background: The Socio-Technical Allocation of Resources (STAR) has been developed for value for money analysis of health services through stakeholder workshops. This article reports on its application for prioritization of interventions within public health programmes. Methods: The STAR tool was used by identifying costs and service activity for interventions within commissioned public health programmes, with benefits estimated from the literature on economic evaluations in terms of costs per Quality-Adjusted Life Years (QALYs); consensus on how these QALY values applied to local services was obtained with local commissioners. Results: Local cost-effectiveness estimates could be made for some interventions. Methodological issues arose from gaps in the evidence base for other interventions, inability to closely match some performance monitoring data with interventions, and disparate time horizons of published QALY data. Practical adjustment for these issues included using population prevalences and utility states where intervention specific evidence was lacking, and subdivision of large contracts into specific intervention costs using staffing ratios. The STAR approach proved useful in informing commissioning decisions and understanding the relative value of local public health interventions Conclusions: Further work is needed to improve robustness of the process and develop a visualization tool for use by public health departments.